Emarketplace Performance Analysis Using PIECES Method - Munirul Ula; Rizal Tjut Adek; Bustami Bustami (International Journal of Engineering, Science and Information Technology, 2021)
E-Marketplace is a place in cyberspace where prospective buyers meet each other to conduct transactions electronically through the internet medium. Like the market in the conventional sense, namely a meeting place for sellers and buyers, in the E-Marketplace, various companies in the world also interact without being limited by the territory of space (geography) and time. Therefore, an analysis of the performance of the website is needed to ensure the performance of the Bireuen emarketplace (meukat.com) website can run effectively in the future. The role of this emarketplace is very important, therefore in building emarketplace we must pay attention to several factors, namely: performance, information, economic, control, efficiency, and service, which is better known as the PIECES method. To analyze the performance of our self-developed emarketplace, was done by PIECES method. While the testing method in the performance analysis of the website uses the GTMetrix and Google Transparency applications. The results of the PIECES questionnaire on the dimensions of Information, Economy, Efficiency, and Service. The average score for the all dimensions is moderate, it is ranging from 42.8% to 51.45% and is in line with the expectations. The GTMetric test results of the Emarketplace website, shows that the average performance grade is 66% or grade D. This means that the quality of the Emarketplace website based on the index generated by Google is still low. It should be improved to provide good quality of service for users in future. The Emarketplace are also being analyzed by the Google transparency report, the result is “no unsafe content” was found, means this website is safe to visit. There are no applications that harm the users.